Reflexiones en torno al papel de los cristianos frente a los derechos humanos en Colombia (2012)
In this text, the author goes around the history of the Human Rights’ consolidation process in the west, considering in turn how these were interpreted and assimilated in the Colombian society during the second half of the 20th century. In this regard, the author points out some obstacles that from a socio-political point of view, have made impossible the real experience on Human Rights in Colombia. The author concentrates his reflection on the experiential perspective of the Christian creed and its contribution to the consolidation of a culture on human rights in our country.